EFFICIENCY OF COMBINATION TREATMENT IN OUTPATIENTS WITH NEW-ONSET PULMONARY TUBERCULOSIS - E. V. Glotova; T. V. Chebotareva; L. I. Oblogina; R. Yu. Abdullaev (Туберкулез и болезни лёгких)
The results of clinical, radiological, and laboratory examinations were analyzed in 126 patients with new-onset pulmonary tuberculosis of small extent were analyzed. The comparative efficiency of treatment in out- and inpatient settings was investigated. Indications for outpatient treatment in a low-incidence region and for in-home treatment were defined.